The Dangerous Lover : Gothic Villains, Byronism, and the Nineteenth-Century Seduction Narrative - Lutz, Deborah (Book collections on Project MUSE., 2006)
"The Dangerous Lover takes seriously the ubiquity of the brooding romantic hero - his dark past, his remorseful and rebellious exile from comfortable everyday living. Deborah Lutz traces the recent history of this figure, through the melancholy iconoclasm of the Romantics, the lost soul redeemed by love of the Brontes, and the tormented individualism of twentieth-century love narratives. The Dangerous Lover is the first book-length study of this pervasive literary hero; it also challenges the tendency of sophisticated philosophical readings of popular narratives and culture to focus on male-coded genres. In its conjunction of high and low literary forms, this volume explores new historical and cultural framings for female-coded popular narratives."